Communication Strategies and the Relevance of Al Wa'iyah's Da'wah Messages on YouTube for Young People by Ustadz Hanan Attaki - Siti Sri Wahyuningsi; Abu Khaer (Jurnal Ilmiah Syi'ar, 2025)
The development of digital technology has changed the way religious preaching is delivered in the modern era, especially for millennials who prefer religious content that is light, relevant, and easily accessible through social media. This study aims to analyze the communication strategies of al-wa’iyah (consciousness-based da’wah) employed by Ustadz Hanan Attaki in his video lecture titled “Islam and the Spirit of Nationalism” on the YouTube channel @HananAttaki. Dakwah is a form of communication that conveys religious values, so the strategies used in its delivery significantly influence the effectiveness of the message. This study employs a qualitative descriptive method with data collection techniques involving observation and documentation of the video content.The results show that Ustadz Hanan Attaki successfully integrates Islamic values and nationalism harmoniously through a relaxed, emotional, and narrative communication approach. He uses simple and contemporary language, incorporates stories relevant to young people’s lives, and presents modern, engaging visuals. The use of digital multi-platforms such as YouTube also expands the reach of his da'wah. This strategy makes the da'wah message easy to understand, emotionally impactful, and aligned with the spiritual needs of the younger generation. In conclusion, Ustadz Hanan Attaki's communication approach is effective in fostering Islamic understanding and nationalistic spirit among millennials.